Settled immigrants in the city of Malaga: local host context and crime. - García-España, Elisa; Aguilar Jurado, Juan Antonio; Contreras Román, María (Universidad del País Vasco, 2020)
Spain is one of the European countries where the immigrant population has grown the most during the first years of this century. However, crime rates have remained constant in this period, even have decreased slightly, so the evolution of both phenomena does not allow to establish a positive relationship between them. Nevertheless, empirical evidence has shown that the immigration experiences differ according to local host conditions. In this way, the context would facilitate the involvement of immigrants in criminal activities. Empirical studies that address the family and social circumstances of immigrants at the local level and from a criminological perspective have not been carried out in Spain. To fill this gap, 173 immigrants were interviewed between 2017 and 2018, in order to study the relationship between local host conditions and self-reported crime, victimisation, and the perception about social control. Findings indicate that a troubled neighbourhood explains the crime committed by immigrants and their victimisation, that committing crimes and being a victim is related, and that immigrants who have committed a crime or have been victim of crime do not have a good opinion about the police and criminal justice system.
Keywords: Málaga - Inmigración; Emigración e inmigración - Delitos; Immigration; Local context; Integration; Crime; Legitimacy